"I had a big bias": disrupting children's biases, stereotypes through studying cultures. Issue 1 (12th May 2021) - Torres, Heidi J.
Abstract : Purpose: This article describes a study examining the influence of a curricular intervention on 25 third-graders' stereotypes and biases related to world cultures and the people who embody them. Design/methodology/approach: The qualitative study focused on privileging student voice through an inductive analytical approach. Triangulated data sources include focus group and paired interviews, recorded lessons, student and teacher curricular documents, as well as field notes. Findings: Results—primarily reported through the children's own thoughts and voices—describe students' initial ideas about world cultures and people prior to experiencing the curriculum, and afterward, documenting shifts in stereotypical beliefs and biased attitudes. Findings indicate many students made positive changes, altering incorrect assumptions about other cultures and people. In addition, some children became able to recognize stereotypes and biases, generalize what they learned to other situations beyond those addressed in the curriculum and identify their own bias. Originality/value: This study provides insight into an understudied topic and population in social studies education. It presents evidence that young children are capable of successfully engaging with the complex topics of bias and stereotypes in meaningful ways, thus providing a rationale for addressing stereotypes and bias concerning world cultures in elementary classrooms.